2019
DOI: 10.1111/asj.13244
|View full text |Cite
|
Sign up to set email alerts
|

Influences of fermentation and ripening temperatures on the enzymatic activity and physicochemical and sensory properties of salted egg white sufu

Abstract: This study developed a novel form of sufu. Salted egg white sufu (SEWS) was produced by fermenting steamed salted egg white with douchi koji and ripening at 25°C, 35°C, or 45°C for 19 days. The results show that the protease activity of the koji reduced pronouncedly during fermentation, whereas the one in the SEWS initially increased but subsequently decreased. The total nitrogen and amino nitrogen contents and degree of protein hydrolysis increased during fermentation and decreased during preripening. SEWS, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Glu was generally considered being one of the important contributors to the taste of soybean fermentation products, and its accumulation may be related to A.oryzae (Li et al, 2010). In addition, Chen et al (2019) also mentioned that the hydrolysis process of raw materials may also release amino acids, resulting in the increase of Glu. Previous studies showed that Glu, Leu, Asp, Ala, Phe, and Lys in white and red sufu were abundance (Han et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Glu was generally considered being one of the important contributors to the taste of soybean fermentation products, and its accumulation may be related to A.oryzae (Li et al, 2010). In addition, Chen et al (2019) also mentioned that the hydrolysis process of raw materials may also release amino acids, resulting in the increase of Glu. Previous studies showed that Glu, Leu, Asp, Ala, Phe, and Lys in white and red sufu were abundance (Han et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Research on the utilization of water hyacinth for alternative energy has been conducted, such as the utilization of water hyacinth for biogas [5], water hyacinth briquettes by combining with plastic waste [6], and water hyacinth for briquettes [7]. The manufacture of SDES generally begins with a salt soaking process for about 21 days [8], then continues with steaming or boiling [9] and the smoked process [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on the process of SDEs were carried out by [8] [9] [11] [12] [13]. The research for SDEs was conducted by [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, soybean is fermented to produce sufu . We have developed a new salted egg white sufu (SEWS) by using salted egg white as the substrate, which is inoculated with douchi koji and then fermented and ripened (Chen et al., 2019). Although this newly developed SEWS has been proved well‐accepted, the microbial changes that occur during its processing have been not elucidated.…”
Section: Introductionmentioning
confidence: 99%